(untitled) - Hill, Charles W. L. (Boston, 1999)
This book introduce about country factors, the global trade and investment environment. The global montary system. The strategy and structure of international business...
Keywords: International business enterprises,Competition, International,Danh nghiệp kinh doanh quốc tế,Cạnh tranh, quốc tế; Management